2011
DOI: 10.1128/aac.05529-11
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Combination Antiviral Drug for Pandemic H1N1 Influenza Virus Infection in Critically Ill Patients on Mechanical Ventilation

Abstract: A recent in vitro study showed that the three compounds of antiviral drugs with different mechanisms of action (amantadine, ribavirin, and oseltamivir) could result in synergistic antiviral activity against influenza virus. However, no clinical studies have evaluated the efficacy and safety of combination antiviral therapy in patients with severe influenza illness. A total of 245 adult patients who were critically ill with confirmed pandemic influenza A/H1N1 2009 (pH1N1) virus infection and were admitted to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 36 publications
(41 reference statements)
0
38
0
Order By: Relevance
“…In anecdotal studies, ribavirin served as a last resort to treat (multi)drug-resistant influenza infections in immunocompromised patients (20,21). The known hematological toxicity of ribavirin seems not to occur during shortterm influenza treatment (22).…”
mentioning
confidence: 99%
“…In anecdotal studies, ribavirin served as a last resort to treat (multi)drug-resistant influenza infections in immunocompromised patients (20,21). The known hematological toxicity of ribavirin seems not to occur during shortterm influenza treatment (22).…”
mentioning
confidence: 99%
“…Regarding TCAD, Kim et al (11) reported lower 14-and 90-day mortalities in a TCAD group than in an oseltamivir monotherapy group (17z versus 35z and 46z versus 59z, respectively). However, the virological clearance in each group was not evaluated, and the differences in mortality were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, TCAD impeded the selection of drug-resistant influenza A in vitro (9). However, clinical data on the efficacy of TCAD remain scarce (10,11). , which shows similar sensitivity to conventional PCR (13), and Seeplex Influenza A/B OneStep Typing (Seegene, Seoul, Korea).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report showed that a triple therapy with oseltamivir, amantadine, and ribavirin, having different active sites, provided not only an in vivo synergic effect on a seasonal influenza virus but also a synergic effect on a seasonal influenza virus presenting resistance to one drug [17]. With regard to the clinical usefulness of such a triple combination therapy, a retrospective study that compared the treatment result of oseltamivir monotherapy with that of oseltamivir, amantadine, and ribavirin combination therapy in severe influenza patients admitted to an intensive care unit during the epidemic period of the pandemic H1N1 in 2009 showed that the 14-day mortality and 90-day mortality were lower in the case of the combination therapy compared to the case of the monotherapy, but the difference was not significant [18]. In another study conducted with H1N1 infected patients who were admitted to an intensive care unit in 2009, a combination of antiviral agents did not show a better survival rate than that of a monotherapy [19,20].…”
Section: Key Question 3: Should Antiviral Combination Therapy Be Usedmentioning
confidence: 99%